Applying boundary element method to simulate a high-skew Controllable Pitch Propeller with different hub diameters for preliminary design purposes. Issue 1 (1st January 2020) - Pourmostafa, Mehdi; Ghadimi, Parviz
Abstract: Using the controllable pitch propeller (CPP) in marine propulsion system makes it possible to have maximum ship speed and low fuel consumption at different engine rpm. Good maneuverability is another advantage of such propeller. This feature has persuaded designers to use CPP in ships with various mission profiles like tugs or ferries. The hub boss is of great importance in CP Propellers because it provides housing for blade actuation mechanism. On the other hand, hub boss geometry should be selected as small as possible since it has negative effect on hydrodynamic performance of propeller, specially its thrust and efficiency. In this article, a 3D potential flow-based solver is developed to predict the hydrodynamic characteristic of marine propellers for preliminary and basic design purposes. Through applying the time stepping scheme, it is possible to generate the rollup wake pattern at each time step. As a result, the interaction of vortex wake-lifting/non-lifting bodies are correctly taken into consideration. Validation of the proposed numerical model is carried out with two standard marine propellers (DTMB4119 and KP505) and a high skewed B-series Controllable Pitch Propeller (CPP). Subsequently, a series of parametric simulations are performed on different non-dimensional hub diameters of a CP propeller to find an appropriate hub diameter (big enough to provide CPP mechanism) with highest propeller performance. Ultimately, the suitable hub diameter is determined for an appropriate design of a CP propeller. Rollup pattern for the RV propeller with different hub diameters.